MENINGKATKAN MINAT BELAJAR MATA PELAJARAN SEJARAH DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN INTERAKTIF“WORDWALL” DI KELAS X TE 2 - Wahyu Adya Lestariningsih (Historia Pedagogia, 2024)
The purpose of this study was to determine student’s interest in learning in subjects using interactive learning media carried out at SMK Negeri 7 Semarang class X TE 2. This type of research is a type of classroom action research carried out in a qualitative way. The technique used for data collection was carried out by means of observation, cycle I, cycle II, and interviews with students in class X TE 4 SMK Negeri 7 Semarang. The analysis used is interactive analysis and data analysis that has been carried out using a data questionnaire distributed to students. Interest in learning history at SMK Negeri 7 Semarang in class X TE 2 increased when interactive learning media was added to history learning, because this was considered to be very helpful for students in unraveling the boredom of learning history in the last hour.